Strategi Kepala Madrasah Aliyah Swasta Al Falah Wuluhan Jember Menuju Madrasah Unggul - Maisyaroh, Anny (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2024)
This study aims to describe and analyze the strategy of the head of MAS Al Falah Wuluhan Jember towards superior madrasah covering aspects of input, process, and output. This research approach uses qualitative with a descriptive type of research. The subjects of this study were the heads of madrasahs, waka curricula, and waka students who were selected by purposive sampling. Data collection techniques include observation, interviews, and documentation. Data analysis using the Miles, Huberman, and Saldana models is data condensation, data presentation, and conclusion drawing or verification. The results showed that the strategy of the head of the private aliyah madrasah Al Falah Wuluhan Jember towards a superior madrasah included through good recruitment of students, increasing human resources, improving madrasah infrastructure, development of superior programs, establish cooperation with various parties and create excellent graduates.